Mixed neuroendocrine-non-neuroendocrine neoplasm of the gallbladder: case report and literature review - Xu Ren; Hong Jiang; Kan Sun; Xufu Qin; Yongping Qu; Tian Xia; Yan Chen (BMC, 2022)
Abstract Background Mixed neuroendocrine-non-neuroendocrine neoplasms (MiNENs) of the gallbladder are rare malignancies. Here we presented two cases and reviewed the related literature. Case presentation Our two patients were postoperatively diagnosed with gallbladder MiNENs, which pathologically consisted of a large cell neuroendocrine carcinoma and papillary adenocarcinoma. After cholecystectomy, one patient had a survival time of 30 months, while the other remained alive through 12 months of follow-up. In the literature, a total of 72 cases of gallbladder MiNENs were identified, and with our two patients included, we calculated a male-to-female ratio of 0.22 and a mean age of 64.5 years for the 74 reported cases. About one-half of these patients were found to have gallstones and presented with abdominal pain or discomfort in a relatively early stage. The preoperative diagnosis of these 74 cases mainly relied on abdominal ultrasound, contrast-enhanced computed tomography (CT) scanning, and magnetic resonance imaging or positron emission tomography/CT. However, the final diagnosis was established based upon the pathological evidence and expression of synaptophysin (Syn) and/or chromogranin A identified by immunohistochemical staining or neurosecretory granules detected by electron microscopy. Fifty-eight patients (78.4%) underwent various operations including simple cholecystectomy (n = 14), en bloc cholecystectomy (n = 9), standard or non-standard radical cholecystectomy (n = 25), or extended radical cholecystectomy (n = 6). The mean size of the resected gallbladder masses was 50.8 ± 36.1 mm (n = 63) with regional lymph node metastasis in 37 patients (52.1%), liver invasion or staging greater than T3 in 33 patients (45.8%), and hepatic metastasis in 26 patients (35.1%). The postoperative median survival time was 36 ± 11.42 months (95% confidence interval, 13.62 to 58.38 months). The log-rank analysis did not find that postoperative adjuvant chemotherapy contributed to a longer survival time relative to that among the patients who did not receive chemotherapy (numbers of patients, 15 versus 43; survival times, 36 months versus 30 months, p > 0.05). Conclusions Our two cases and the cases in the literature suggest that MiNENs of the gallbladder predominantly occur in women; are associated with early lymph node metastasis, local hepatic invasion, and hepatic metastasis; and can be managed by various surgeries as well as chemotherapy combined with somatostatin analogs.